A Comparison of Four Planted Species Abilities to Accumulate Cadmium Element (Cd) in Lattakia City (Alfoursan Park) (Latakia University Journal -Biological Sciences Series, 2013)
This study aims to compare the ability of four plant species (Ficus benjamina L., Bougainvillea glabra, Ligustrum vulgare L., Bauhinia variegate Linn.) to absorb and accumulate the cadmium element which is basically emitted by motor vehicles (transportation). The four species were planted in Alfoursan Park in Lattakia City. Samples of leaves, bark, wood and soil were collected, and then processed (drying, digesting and filtrating) for analysis using an atomic absorption spectrophotometer. The results showed that the highest concentration of cadmium was in the bark of Bougainvillea glabra 4.4 ppm (in dry weight), next in the leaves of Bougainvillea glabra 4.2 ppm, then in the bark of Ficus benjamina L. 3.93 ppm, and finally in the bark of Bauhinia variegate Linn. 3.55ppm. The lowest concentration, however, was in the wood of Ficus benjamina L. 1.66 ppm. The results show the importance of the four species and the potential of absorption and accumulation of the cadmium element. Results also showed the superiority of Bougainvillea glabra over Ficus benjamina L., Ligustrum vulgare L. and Bauhinia variegate Linn. Bougainvillea glabra is classified in the study as an accumulator plant important to purify the environment from the cadmium element.